AI: A NEW LONE-WOLF TERRORISM IN THE DIGITAL ERA (PRELIMINARY ANALYSIS) - Anakotta, Marthsian Yeksi, MYA (Journal of Terrorism Studies, 2024)
This article addresses two fundamental inquiries: can AI engage in acts of terrorism? If so, how might such a phenomenon occur? My hypothesis posits that AI is capable of independently committing acts of terrorism, a classification derived from the study of terrorism known as lone-wolf terrorism. To address these dual issues, this article adopts a criminological approach, which is further elaborated through an examination of lone-wolf terrorism and the advancement of artificial intelligence. As is widely recognized, contemporary terrorist organizations have harnessed technological advancements in the realm of information and communication to perpetrate acts of terrorism within the digital sphere. Within the realm of terrorism studies, such activities are categorized as cyber-terrorism, while criminological investigations refer to them as cybercrime. Nonetheless, these forms of criminality are generally carried out by individuals and/or groups (users) who manipulate information and communication systems. Through these channels, content laden with radical-terrorism ideologies is disseminated via social media platforms to facilitate online radicalization and propagate terror campaigns. Ultimately, both endeavors share the objective of recruiting new members who will be assigned tasks or sympathizers who may willingly commit acts of terrorism, whether in the online or offline domains. Drawing upon routine activity theory, the presence and evolution of AI could introduce a novel actor into the sphere of cyber-terrorism, one executed by AI itself. As postulated by routine activity theory, criminal incidents transpire when three elements converge: a motivated offender, a suitable target, and a lack of capable guardianship. While AI possesses cognitive and learning abilities, albeit not yet at the level of human cognition, in the context of cyber-terrorism, the convergence of AI with the elements of a motivated offender, suitable target, and lack of capable guardianship could position it as a novel actor.